Differences in the Relationship between Economic Growth and Population Change in Developing and Developed Countries - Zhuang Zimo (SHS Web of Conferences)
The world’s countless economies are constantly undergoing various changes. This study analyses the role played by population in different levels of economic development, namely developed countries and developing countries, on a national level. The main text is based on theories such as Malthusianism and Boserup theory, combined with case studies of two types of countries represented by Pakistan and Japan, to analyse the relationship between population and economy. In developing countries, the relationship between population changes and economic development is negatively correlated; while in developed countries, the relationship is positively correlated. The next step is to delve into the reasons behind the results obtained from in-depth analysis and explore why there are differences between developed countries and developing countries. Some of the reasons include the baby boom, industrial structure, health care and education. The interplay between these factors and populations has led to economic differences between developed and developing countries.